2020
DOI: 10.1115/1.4047078
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Flow Field Characteristics by Drag Reducing Agent Additives in a Stirred Vessel

Abstract: In this paper, experimental investigation on two oil-soluble drag-reducing agents (DRAs) were carried out in stirred vessel by standard six-blade Rushton, based on the application of particle image velocimeter (PIV). Two DRAs (1# and 2#) with different concentrations from 3 ppm to 50 ppm were added into diesel, respectively, and speed of impeller speed was set 400 rpm. Flow field characteristics including turbulence intensity, turbulent kinetic energy (TKE), and energy dissipation rate (EDR) influenced by thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For example, Dritselis and Vlachos 4 pointed out that copper particles in the fluid would weaken the strength of coherent structures of turbulence and inhibit the development of these structures. Qi et al 5 applied particle image velocimeters (PIV) to the flow field characteristics of two oils in the stirring vessel-soluble drag reducing agent(DRA) found that these additives have an effect on turbulence strength, turbulence kinetic energy (TKE) and energy dissipation rate (EDR) in the stirring vessel. The inhibition of turbulence intensity by DRA at concentrations below 10 ppm is not significant.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dritselis and Vlachos 4 pointed out that copper particles in the fluid would weaken the strength of coherent structures of turbulence and inhibit the development of these structures. Qi et al 5 applied particle image velocimeters (PIV) to the flow field characteristics of two oils in the stirring vessel-soluble drag reducing agent(DRA) found that these additives have an effect on turbulence strength, turbulence kinetic energy (TKE) and energy dissipation rate (EDR) in the stirring vessel. The inhibition of turbulence intensity by DRA at concentrations below 10 ppm is not significant.…”
Section: Introductionmentioning
confidence: 99%